Bone mineral density changes in patients with rheumatoid arthritis - Saleh, Ashna Swara; Media, Shwan K. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Bone loss regarded as a major health concern which is thought to be associated with a number of chronic illnesses including rheumatoid arthritis. This study was designed to determine the frequency of low bone mass as well as the influence of disease duration on bone mass in the patients with rheumatoid arthritis. Methods: Sixty patients with rheumatoid arthritis who were visiting Rizgary Teaching Hospital in Erbil from April 2015 to March 2016were included in a cross-sectional study. Bone mineral density was measured using dual energy X-ray absorptiometry. Results: There was increased frequency of bone loss in patients with rheumatoid arthritis. There was a positive association between bone mineral density of the spine and femoral neck with disease activity measured by disease activity score and disease activity index (P <0.05). There was a significant association between bone mineral density and disease duration. Conclusion: Significant proportions of patients with rheumatoid arthritis have osteoporosis at the femoral neck and lumber spine, and disease duration longer than five years is associated with a significant increase in bone loss.